Exploring the opportunities and challenges of teaching controversial topics in Social Sciences at the Intermediate Phase - Mlambo, Sithembiso (University of the Free State, 2024)
The study investigated the challenges and opportunities that teachers face when teaching controversial topics in the Social Sciences at the Intermediate Phase. Controversial topics, which involve conflicting interests and perspectives, can be emotionally charged and challenging because they arouse emotions among learners. However, teaching such topics can empower learners, foster diversity, enhance subject knowledge, and promote a deeper understanding of justice and inclusivity. This study utilised critical social theory to explore the influence of power dynamics, ideology, and societal structures on knowledge creation. Its goal was to challenge existing norms and promote equity by encouraging critical thinking and open dialogue among learners. A qualitative approach was employed, utilising open-ended interviews and focus group discussions, to investigate teachers’ experiences in teaching controversial topics. A narrative research design was used to explore the complexity and perspectives surrounding the teaching of contentious topics in Social Science classrooms. By comparing and contrasting different narratives, a deeper understanding of the opportunities and challenges encountered by Intermediate Phase teachers when engaging learners on controversial topics was achieved. Thematic analysis was used to generate themes and sub-themes from the transcribed data. Findings revealed that topics like racism, tribal discrimination, gender roles, and religious diversity spark debate and opposing views within communities and the classroom. During interviews teachers explained that inclusive learning settings and critical social theory are essential for transformative learning. By teaching controversial topics, teachers play a crucial role in fostering social awareness, critical thinking and active citizenship skills which expose conscious and unconscious biases among learners. Controversial topics align with curriculum guidelines, such as the United Nations Declaration on the Rights of Indigenous Peoples and South Africa's Social Sciences curriculum, encouraging critical citizenship and understanding of social justice concerns. Teachers in this study acknowledged the impact of cultural origins on teaching contentious subjects such as gender norms, religious diversity, racial and tribal discrimination, and xenophobia. Teachers emphasised the importance of promoting tolerance and diversity in their teaching methods by using case studies, role-playing and multimedia content. They used these techniques to develop empathy and a sense of diversity among learners. They also employed coping strategies, active learning techniques, debates, and multimodal approaches to address systematic disparities and promote inclusivity among learners. The study recommended six strategies for teaching controversial topics in the Intermediate Phase. These are facilitating structured debates, examining the causes of intolerance, community involvement, fostering a culture of trust in teachers, and using case studies. These strategies promote self-reflection, critical thinking and effective communication by exposing learners to diverse perspectives.
Dissertation (M.Ed.(Curriculum Studies))--University of the Free State, 2024
Keywords: Controversial topics; Diversity; Empathy; Intermediate phase teachers; Social sciences